Indian Farming ( June 2019) - ICAR. (India : ICAR, 2019)
THE journal Indian Farming, now in its third year of publication, is issued by the Imperial Council of Agricultural Research of India and is a praiseworthy attempt to bridge the gap between cultivator and scientific worker. It is a monthly with a pleasant appearance of format and is copiously illustrated. It includes articles on breeds of Indian livestock, livestock products and crops, and the erosion problem receives due recognition. Shorter articles and reviews from all parts of the country help to provide a reasonably full conspectus of Indiari agricultural problems and of the manner in which technical effort is being directed to meet them. All original papers have a practical bias, as, for example, the recent paper entitled (3z(BMore Light on the Red-spot Epidemic(3y(B, by B. L. Chona and G. W. Padwick (3, 70-73 ; 1942). This gives details of the infection of sugar-cane by Colletotrichum falcatum, which has led to sudden and almost complete failure of the variety Co 213 over a wide area: a new strain of the fungus, not observed before the epidemic, is described. A note on animal quarantine in the Provinces and States discloses that the Central Provinces alone have anything -like a comprehensive organization. As a good example of the educative article may be mentioned (3z(BPropagation of the Apple in Kumaun(3y(B, by R. S. Singh. The solar treatment of loose smut of wheat-a method evolved at Lyallpur from Jensen's hot-water treatment-has been described by J. C. Luthra (2, 416 ; 1941) ; it is very effective and furnishes a striking instance of extreme simplicity in a control measure well adapted for farmers. A new heavy-yielding and strong-growing variety of sugar-cane (Co 421), described by Ch. Kh. Mohammad (2, 140 ; 1941), seems to be especially suited to the Punjab, and its seed is being multiplied as rapidly as possible. V. R. Rajagopalan (2, 136-39 ; 1942) has established calcium deficiency as the cause of an outbreak of non-bacterial abortion in equines. Indian Farming gives much attention to processing and marketing, including the canning and dairying industries, and the grading of eggs and oranges, and whenever possible simple devices adapted to Indian conditions are described in order that quality shall be improved.s